2016
DOI: 10.1080/14789949.2016.1172658
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and discrimination in mentally disordered offender patients – a comparison with a non-forensic population

Abstract: a Population health research institute, st georges university, london, united Kingdom; b John howard centre, east london foundation Trust, london, united Kingdom; c south london and Maudsley nhs Trust, london, united Kingdom ARTICLE HISTORY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…This may delay treatment and lead to the use of maladaptive coping strategies in place of seeking help. Similarly, perceived stigma in correctional and forensic psychiatry populations has been shown to create barriers to rehabilitation and is related to poor adjustment in the community ( Mezey et al, 2016 ; Moore and Tangney, 2017 ; West et al, 2014 ). Individuals with a criminal history who anticipate stigma have been found to withdraw from social situations in order to avoid stigmatization and discrimination ( Moore and Tangney, 2017 ).…”
Section: Stigmatization and Covid-19mentioning
confidence: 99%
“…This may delay treatment and lead to the use of maladaptive coping strategies in place of seeking help. Similarly, perceived stigma in correctional and forensic psychiatry populations has been shown to create barriers to rehabilitation and is related to poor adjustment in the community ( Mezey et al, 2016 ; Moore and Tangney, 2017 ; West et al, 2014 ). Individuals with a criminal history who anticipate stigma have been found to withdraw from social situations in order to avoid stigmatization and discrimination ( Moore and Tangney, 2017 ).…”
Section: Stigmatization and Covid-19mentioning
confidence: 99%
“…Studies that compared the stigma attached to mental illness in general and when it is linked to offending produced conflicting results. Brooker et al 19 found that respondents were much less sympathetic towards psychiatric patients who had committed a crime, whilst Mezey et al 20 found similar levels of stigma in the general adult and forensic patients. In the current study, participants experienced judgemental attitudes from community members.…”
Section: Discussionmentioning
confidence: 99%
“…According to Sump (2016), married probationers or those who have common partners have more burden or obligation to support their family. Previous studies have confirmed that family, including parents, spouse, and children were the influential factors in the probationers' rehabilitation process or adversely, pushed to become recidivism (Kilmer, 2016;Mezey et al, 2016;Sump, 2016;Rains-Russell, 2009). Out of 17 participants, ten choose to participate in an in-depth interview and seven for the focus group discussion.…”
Section: Methodsmentioning
confidence: 95%